2020
DOI: 10.1186/s13244-020-00914-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasonography in the assessment of anterior knee pain

Abstract: Background Anterior knee pain (AKP) is a problematic complaint, considered to be the most frequent cause of orthopedic consultancy for knee problems. This study aimed to highlight diagnostic accuracy of ultrasonography as a fast imaging technique in assessment of patients with AKP. Methods and results A prospective study was conducted on 143 patients with clinically confirmed AKP. All patients underwent ultrasonography and MRI examinations of the knee. The diagnostic accuracy of ultrasonography compared to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 39 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Tendinopathy is one of the most common causes of acute knee joint pain. In this study, HRS had a sensitivity of 75% and 66.6% in detecting patellar and quadriceps tendinopathy in comparison to 84% and 87.5% reported by Basha et al 17 In this cohort, there was almost perfect agreement with a coefficient κ = 0.85 , which was noted between HRS and MRI, in detection of knee patellar tendinopathy. Likewise, there was substantial agreement with coefficient κ = 0.79 , which was noted between HRS and MRI, in detection of knee quadriceps tendinopathy.…”
Section: Discussionsupporting
confidence: 64%
“…Tendinopathy is one of the most common causes of acute knee joint pain. In this study, HRS had a sensitivity of 75% and 66.6% in detecting patellar and quadriceps tendinopathy in comparison to 84% and 87.5% reported by Basha et al 17 In this cohort, there was almost perfect agreement with a coefficient κ = 0.85 , which was noted between HRS and MRI, in detection of knee patellar tendinopathy. Likewise, there was substantial agreement with coefficient κ = 0.79 , which was noted between HRS and MRI, in detection of knee quadriceps tendinopathy.…”
Section: Discussionsupporting
confidence: 64%
“…In suspected medial plica, dynamic sonography had diagnostic accuracy, sensitivity, and specificity of 88%, 90%, and 83%, respectively [77,78]. The US is useful in detecting supra-patellar and all medial patellar plicae but not infrapatellar plicae [52]. In the present study, we defined synovial plica in over 70% of patients.…”
Section: Synovial Plica and Lipoma Arborescencementioning
confidence: 70%
“…In another study, Basha et al reported US and MRI findings in anterior knee pain (AKP); joint effusion was the most common (38%), followed by trochlear cartilage defect (20.6%) and superficial infrapatellar subcutaneous edema (20%) [52]. Draghi et al demonstrated the US's sensitivity and specificity of 81.3% and 100% specificity in knee effusion [41].…”
Section: Reduced Cartilage Thickness Osteophyte Formation and Effusio...mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies with B-Mode imaging, echogenicity of the edematous QFP was recorded as hypoechoic; however, it has not been stated which tissue was used in comparison (25,26). In the current study, QFP echogenicity was either hyperechoic or isoechoic when compared with the subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 99%